Temperature impact on the micro-structures and mechanical properties of high-strength engineered cementitious composites. (30th November 2019) - Luo, Jianjun; Cai, Ziwei; Yu, Kequan; Zhu, Wenjun; Lu, Zhoudao
Highlights: High-temperature influence on the mechanics of high-strength PE-ECC was investigated. Tendencies of mechanical properties with temperatures were established. A microscale study of post-high temperature specimens was conducted. Abstract: The present research aimed to investigate the temperature impact on the mechanical properties of high-strength engineered cementitious composites (HS-ECC). Five temperatures, i.e., 20, 50, 100, 140 and 200 °C, were set to study the mechanical properties including the uniaxial tensile, flexural and compressive properties. The results show that heating temperatures had a decisive influence on the mechanical behavior of HS-ECC and benefited the mechanical properties of HS-ECC specimens up to 50 °C. The tensile and flexural specimens exhibited the multi-crack and strain-hardening behavior up to 140 °C, while a brittle failure occurred at 200 °C due to the melting of fibers. The compressive strength of HS-ECC decreased sharply from 86.0 MPa at 20 °C to 42.6 MPa at 200 °C. The micro-structures of post-high-temperature HS-ECC specimen were determined by the scanning electron microscope (SEM) and mercury intrusion porosimetry (MIP) tests. The SEM results show that the thermal effect was detrimental to the fiber morphology, while the MIP results show the significant coarsening effect of high temperature on the pore size of HS-ECC matrix.